Polygamy and the best interests of the child: an analysis of the law in Kenya - Koech, F. J. (Strathmore University, 2025)
Polygamy, a deeply rooted cultural practice in Kenya, presents significant challenges in ensuring fairness and justice for all parties involved, particularly children. This study examines the impact of polygamy on children and examines the adequacy of the Kenyan legal framework in safeguarding their best interests. Anchored in the best interest principle outlined in the United Nations Convention on the Rights of the Child (UNCRC), the study evaluates Kenya’s Children Act (2022) to determine its adequacy in addressing the unique challenges faced by children in polygamous customary unions. Applying a doctrinal research methodology, the study draws insights from existing literature on the impacts of polygamy on children. Findings reveal significant emotional, psychological, social, and financial neglect experienced by children in these unions, often stemming from a lack of equitable resource distribution and emotional support from fathers. Additionally, the study identifies a critical gap in Kenyan law where existing provisions inadequately address the specific needs of children in polygamous customary settings application of the best interest principle. The study concludes by proposing targeted legal reforms to enhance the protection of children’s rights in polygamous unions. Key words: Polygamy, Children Act 2022, Best Interest Principle, Child’s rights.
Full - text undergraduate research project